In situ coupling of chitosan onto polypropylene foils by an Atmospheric Pressure Air Glow Discharge with a liquid cathode. (10th December 2016) - Nikitin, D.; Choukourov, A.; Titov, V.; Kuzmicheva, L.; Lipatova, I.; Mezina, E.; Aleksandriiskii, V.; Shelemin, A.; Khalakhan, I.; Slavinska, D.; Biederman, H.
Highlights: Atmospheric plasma induces fragmentation of chitosan macromolecules in water solution. Energetic yield of bond scission is higher than in ultrasonic or UV methods. Chitosan strongly binds to polypropylene immersed into plasma activated solution. Abstract: Atmospheric air plasma treatment of chitosan solutions leads to degradation of chitosan molecules by OH radicals and is accompanied by a predominant cleavage of glycosidic linkages and by a decrease of the molecular weight. The degradation proceeds via first order kinetics with the rate constant of (5.73 ± 0.22) × 10 −6  s −1 and the energetic yield of chitosan bond scission of (2.4 ± 0.2) × 10 −8  mol/J. Products of degradation together with intact chitosan molecules adsorb and form coatings on polypropylene foils immersed into the solution that is being plasma treated. The plasma treatment results in strong binding of chitosan to polypropylene due to the formation of covalent bonds between the activated polymer surface and chitosan molecules. Plasma-driven crosslinking is responsible for the accumulation of compressive stress which leads to the development of buckling instabilities in the chitosan coatings.